История одного города - Салтыков-Щедрин Михаил Евграфович (Детская литература, 1981)
Экземпляры: ДО (20200630) / Инвентарный номер: 2236 / Цена: 500.00 / Сис.шифр: 84 / Авт.знак: С 16 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)1